Personalised Profiling of Innate Immune Memory Induced by Nano-Imaging Particles in Human Monocytes - Della Camera, Giacomo; Madej, Mariusz; Ferretti, Anna Maria; La Spina, Rita; Li, Yang; Corteggio, Annunziata; Heinzl, Tommaso; Swartzwelter, Benjamin J.; Sipos, Gergö; Gioria, Sabrina; Ponti, Alessandro; Boraschi, Diana; et al. (Frontiers in Immunology, 2021)
Engineered nanoparticles used for medical purposes must meet stringent safety criteria, which include immunosafety, i.e., the inability to activate possibly detrimental immune/inflammatory effects. Even medical nanomaterials devoid of direct immunotoxic or inflammatory effects may have an impact on human health if able to modify innate memory, which is the ability to “prime” future immune responses towards a different, possibly more detrimental reactivity. Although innate memory is usually protective, anomalous innate memory responses may be at the basis of immune pathologies. In this study, we have examined the ability of two nanomaterials commonly used for diagnostic imaging purposes, gold and iron oxide nanoparticles, to induce or modulate innate memory, using an in vitro model based on human primary monocytes. Monocytes were exposed in culture to nanoparticles alone or together with the bacterial agent LPS (priming phase/primary response), then rested for six days (extinction phase), and eventually challenged with LPS (memory/secondary response). The memory response to the LPS challenge was measured as changes in the production of inflammatory (TNF, IL-6) and anti-inflammatory cytokines (IL-10, IL-1Ra), as compared to unprimed monocytes. The results show that both types of nanoparticles can have an effect in the induction of memory, with changes observed in the cytokine production. By comparing nanomaterials of different shapes (spherical vs. rod-shaped gold particles) and different size (17 vs. 22 nm diameter spherical iron oxide particles), it was evident that innate memory could be differentially induced and modulated depending on size, shape and chemical composition. However, the main finding was that the innate memory effect of the particles was strongly donor-dependent, with monocytes from each donor showing a distinct memory profile upon priming with the same particles, thereby making impossible to draw general conclusions on the particle effects. Thus, in order to predict the effect of imaging nanoparticles on the innate memory of patients, a personalised profiling would be required, able to take in consideration the peculiarities of the individual innate immune reactivity.